2020
DOI: 10.1177/1044389419895853
|View full text |Cite
|
Sign up to set email alerts
|

Can Family and Neighborhood Cohesiveness Buffer the Association Between Family Economic Hardship and Children’s Peer Victimization?

Abstract: The aim of the current study is to identify factors that buffer the link between family economic hardship and peer victimization. We examined whether family and neighborhood cohesiveness moderated the association between family economic hardship and children’s peer victimization. Data were derived from the 2016 National Survey of Children’s Health, and the total sample was 14,155 caregivers who responded to questions about children, aged 6 through 11 years old. Analyses included bivariate correlations and hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…2 YU or adolescence, identifying cohesion as a key protective factor in promoting socioemotional health of young people (Fosco & Lydon-Staley, 2020;Hong et al, 2020;Lucia & Breslau, 2006).…”
Section: Transactions Between Family Cohesion and Children's Internal...mentioning
confidence: 99%
See 2 more Smart Citations
“…2 YU or adolescence, identifying cohesion as a key protective factor in promoting socioemotional health of young people (Fosco & Lydon-Staley, 2020;Hong et al, 2020;Lucia & Breslau, 2006).…”
Section: Transactions Between Family Cohesion and Children's Internal...mentioning
confidence: 99%
“…Cohesion can foster a sense of support and connectedness in children, providing them with the necessary emotional and practical support that contribute to their positive socioemotional development (Fosco & Lydon-Staley, 2020; Hong et al, 2020; Olson, 2000; Renzaho et al, 2013). A few studies found cohesion to be inversely associated with internalizing/externalizing problems or peer victimization in children in middle childhood or adolescence, identifying cohesion as a key protective factor in promoting socioemotional health of young people (Fosco & Lydon-Staley, 2020; Hong et al, 2020; Lucia & Breslau, 2006).…”
Section: Transactions Between Maternal and Paternal Psychological Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…Neighborhood social processes have been shown to mediate the risk of adolescent victimization, including in economically distressed neighborhoods (Hong, Song, Peguero, Wu, & Schmaeman, 2020;Lenzi et al, 2012). Studies have found that informal social control, the willingness of neighborhood residents to intervene to manage children's behavior and foster norms for caring for public spaces, is associated with lower neighborhood crime rates (Gorman- Smith & Schoeny, 2010).…”
Section: Safetymentioning
confidence: 99%
“…Cohesion can facilitate a sense of support and connectedness in children, which can contribute to their positive socioemotional development [5,13,14]. A few studies found cohesion to be inversely associated with internalizing problems or peer victimization in children in middle childhood or adolescence [13][14][15].…”
Section: Introductionmentioning
confidence: 99%